Analisis Pendapatan dan Efisiensi Usaha Produk Olahan Udang di Kepenghuluan Sungai Nyamuk Kecamatan Sinaboi Kabupaten Rokan Hilir - Yuyunisari Yuyunisari; Mailisa Mailisa; Febrina Ramadhani; Indah Fitriani (Pusat Riset dan Inovasi Nasional, 2025)
Kepenghuluan Sungai Nyamuk, Sinaboi District, utilizes maritime potential with abundant sea catches as the main source of income. This study analyzes the income and efficiency of shrimp processing businesses, including shrimp crackers. The method used is a survey with a purposive sampling tech-nique. Data were obtained through observation, interviews, and literature. The results of the analysis show that the shrimp cracker processing business has an R/C ratio of 1.89. This value indicates that this business is efficient and feasible to be developed because every expenditure of 1 rupiah can generate income of more than 1 rupiah. The average income per shrimp cracker production is IDR 642,116.77, with a total cost of shrimp crackers of IDR 717,883.23 Based on the results of the study, the shrimp processing business in Kepenghuluan Sungai Nyamuk, Sinaboi District, Rokan Hilir Regency has proven to be financially feasible and has great potential to be further developed.